Two cases of progressive familial intrahepatic cholestasis type 2: Role of surgery with brief review of literature - Hinglaj Saha; Ghosh Tapanjyoti; Somak Biswas; Prafulla Kumar Mishra; Kalyani Saha Basu; Uttara Chatterjee (Wolters Kluwer Medknow Publications, 2019)
Progressive familial intrahepatic cholestasis (PFIC) is a rare bile acid transporter defect and autosomal recessive disorder with type 2 being the most common type. Partial internal or external biliary diversion delays its progression to end-stage liver disease. Here, we discuss two cases of type 2 PFIC.